Demographic transition for economic development in Taipei,China: Literature and policy implications - Chin-peng Chu; Kuo-chun Yeh (Asian Development Bank Institute (ADBI), 2021)
As an economy with a population of 23 million, Taipei,China is enjoying the demographic dividend of economic growth resulting from a shift in the population age structure, but an increasingly aged population could be bad for the economy. As an international comparison, its population is aging faster than that of most members of the Asian Development Bank and other advanced economies. Based on the literature, this paper contributes to the evaluation of the impact of aging on economic growth and volatility using relevant data and then concludes with the government policies relevant to the prospective aging problem. At the current stage, the situation is not as bad as expected. An aging workforce with positive productivity has no negative impact on economic growth. The old-age dependency ratio has a significantly negative effect on economic development, but appropriate foreign labor immigration and elderly long-term care policies can mitigate it. Higher education attainment still works to support economic growth in the long run. Besides, an increase in longevity first enhances and then erodes net foreign assets, and high old-age dependency ratios cause investments to respond strongly to technology shocks because individuals prefer to save more for retirement in aging societies. However, population aging has a minor influence on the dynamics of the macroeconomic variables. Nevertheless, the government should be cautious and allocate resources to help labor-intensive and low-skilled industries transform into more innovation-oriented and knowledge-intensive ones. Social welfare support must also become an important aspect of the social security framework.
Keywords: J11; J18; 330; population aging; economic growth; net foreign assets; demographic policy; health care; Taipei; China